Asian Development Review. (Metro Manila, Philippines Asian Development Bank, 2017)
This issue discusses growth convergence paths in Asia and the middle income trap, impacts of minimum wage on employment and earnings for men and women in India, and working conditions in developing economies, among others.
Keywords: Economics; Energy -- Economic aspects; Electronic books